Heterotopic pregnancy: a case series - Mounir, Moukit; Rahmoune, Mohammed; Allilou, Ismail; Elmoubakkir, Bouchra; Laghzaoui, Omar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Heterotopic pregnancy once considered a rare phenomenon is now thought to be more common as the overall incidence of ectopic pregnancy continues to increase. We report a series of six cases of heterotopic pregnancies seen in our department over a period of seven years. Two of these occurred after assisted reproductive techniques; while the other cases were spontaneous heterotopic pregnancies. The clinical presentation of these cases was varied with late diagnosis occurring in two cases. Preservation of the intrauterine pregnancy was obtained in four cases. Unfortunately, the other cases were aborted spontaneously on the postoperative period. Only with an early diagnosis and adequate management the intrauterine pregnancies will reach viability, with a great chance of a favorable obstetric outcome.